Effect of Cr3+ concentration on structural and optical properties of ZnAl2O4:Cr3+ - Loan, Tran Thi; Ha, Le Hong; Long, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 26 No 1, 2010)
Abstract